A double metacercarial infection in an Indian fresh water fish, Heteropneustis fossilis (Bloch) - Chakrabarti, K. K. (1969)
A new species of strigeid metacercaria, Tetracatyle muscularis was found in an Indian fresh water fish, Heteropneustis fossilis (Bloch). The metacercarial cysts were embedded in the subrutaneous tissue of the host. Metacercaria is chiefly characterized by having its spinose body divided into a fore-body and a hind-body, oral sucker larger than ventral sucker, and H-shaped posterior testis.